The Influence of Product Quality, Promotion and Price on Purchasing Decisions - Islahuben Islahuben; C. Catur Widayati; Yenita Yenita; L. Setya Budiawan (DINASTI RESEARCH, 2023)
This study aims to analyze the Purchase Decision at the Wuling Car Showroom in Fatmawati, South Jakarta. This study uses SEM data analysis techniques and data processing using PLS 4.0. The population is the Jakarta community, which has a minimum income of Rp. 4,000,000 with a sample of 135 respondents. The sampling technique used was Pourposive Sampling. By using a quantitative descriptive approach. The results of this study indicate that Product Quality has a significant positive effect on Purchase Decisions, Promotion has a significant positive effect on Purchase Decisions and Price has a significant positive effect on Purchase Decisions.